Trade and employment : a study of the effects of trade expansion on employment in developing and developed countries - Lydall, Harold; International Labour Office (Geneva : International Labour Office, 1975)
The main purpose of the study, which was carried out within the Economic Analysis Programme of the ILO, is to estimate the likely effects on employment in developed and developing countries respectively of an increase in exports of selected products from developing to developed countries
Includes bibliographical references.
osc 29/01/2019
Loans
Keywords: Labor supply; Commerce; Developing countries